2022
DOI: 10.17219/acem/146797
|View full text |Cite
|
Sign up to set email alerts
|

Various clinical scenarios of primary melanoma of the esophagus: A retrospective 20-year analysis from two university thoracic surgery centers

Abstract: Background. Primary melanoma of the esophagus (PME) represents a rare type of gastrointestinal malignancy with an exceptionally poor diagnosis. So far, only few descriptions of PME which satisfactorily summarize their clinical characteristics and prognosis have been published.Objectives. The aim of our study was to summarize our experience with PME patients. Materials and methods.In a group of 1387 patients who underwent esophagectomy due to neoplastic process in the years 2000-2020 in 2 high-volume university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Although Nivolumab has been shown to be less effective in mucosal melanomas than in cutaneous melanomas, the standard treatment and efficacy of ICI in PMME remain unclear due to its rarity [ 275 , 288 , 289 , 290 , 291 , 292 , 293 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 , 304 ]. As we have analyzed, some studies have revealed promising results, but there is a need for randomized controlled trials with larger series of PMME patients [ 186 , 218 , 275 , 305 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Nivolumab has been shown to be less effective in mucosal melanomas than in cutaneous melanomas, the standard treatment and efficacy of ICI in PMME remain unclear due to its rarity [ 275 , 288 , 289 , 290 , 291 , 292 , 293 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 , 304 ]. As we have analyzed, some studies have revealed promising results, but there is a need for randomized controlled trials with larger series of PMME patients [ 186 , 218 , 275 , 305 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the greater diffusion of molecular biology techniques such as next generation sequence (NGS) and parallel massive sequencing have made it possible to deepen the knowledge related to PMME by analyzing the different mutations responsible for this entity [ 275 , 289 , 291 , 292 , 293 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 ]. More specifically, in a very recent work, Tsuyama et al studied 13 cases of PMME and 10 cases of malignant skin melanoma (SKMM) with NGS and immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%